The Impact Analysis of Electricity Prices on the Energy Intensity of the Kazakhstani Economy and Sustainable Development - Tulaganov, Anvar; Sagindykova, Gulnara; Isaev, Murad; Bimbetova, Bibigul; Kaiyrgaliyeva, Maira; Aidosova, Bakhitzhamal; Orynbassarova, Aizhan (International Journal of Energy Economics and Policy, 2022)
The independent Kazakhstan is highly inefficient electricity production, transmission and distribution infrastructure, while electricity prices both for industry and residential consumers is significantly lower that world average level due to abundance of oil, gas and coal resources. As a result of resource usage inefficiency, the country loss of 3-5% of national growth domestic product and competitiveness on international economic arena. The aim of this study is to determine the possibilities of ensuring economic growth in Kazakhstan by improving the energy efficiency of the economy. The paper proposes to identify the relationship between economic growth and energy efficiency in Kazakhstan by applying the correlation-regression and comparative analysis of the dynamics of the national gross product and its specific energy intensity, which will determine and substantiate the priority direction of increasing energy efficiency and sustainable development in Kazakhstan. The result of correlation-regression analysis reveals that an increase in the price of electricity supply for industry by 2.5 KZT tenge per 1 kW leads to an improvement in the energy intensity of GDP by 0.012 kg per 47,000 KZT (or 100 USD), and an increase in the price of electricity supply for the population by 2.5 KZT per 1 kW leads to an improvement in energy intensity GDP by 0.005 kg per 47,000 KZT. In discussion, the article argues that country is mostly focuses on development of renewable energy sector, while considering the situation that Kazakhstan is geographically large country with high energy losses during the transmission and distribution electricity system, the application of the Smart Grid technologies seems as a prerequisite for improvement of energy efficiency and economic growth in Kazakhstan.